Treatment with 100 Mg Weekly Leflunomide in Rheumatoid Arthritis-An Open Study - Halil Koyuncu; Neval Bozok; Seçil Yalgın; Fatma Kumbasar; Haluk Aksoy (Archives of Rheumatology, 2007)
Objective: To investigate the efficacy and safety of leflunomide using 100 mg / week in rheumatoid arthritis. Patients and Methods: Patients having active rheumatoid arthritis according to the American Collage of Rheumatology criteria were included. Following of a loading dose of 100 mg of leflunomide for three days they continued with 100 mg of leflunomide weekly. Efficacy and side effects were evaluated. Results: Seven patients mean age was 50.5±6.1 years and the mean duration of the disease was 8.0±5.8 years.All patients had previously taken Disease Modifiying Antirheumatic Drug (DMARDs).There were no who were left the treatment. Pain score was 6.5±0.9 before treatment and 4.1±1.0 after treatment. The number of tender joints 12.7±2.1 at the beginning and 8.5±1.6 at the end of 6 months.The number of the swollen joints was 12.5±3.5 at the beginning of the study and 8.7±2.4 at the end of the study. These differences were statistically significant (p< 0.05). Stanford scala was 45.4±7.8 before treatment and 32.8±6.1 after treatment. General health status mean was 5.0±1.1 at the beginning and 7.4±1.3 at the end.The last both changed significant, also (p<0.05). Arterial tension was at normal limits at the beginning and end of treatment. Erytrocyte sedimentation rate was 62.8±25.6 mm /hour at the beginning and 43.4±11.6 mm/hour at the end of the study. CRP levels were found 39.2±17.5 IU at the beginning and 26.2±10.8 IU at the end. The decreases were significant (p<0.05). ALT were 20.8±8.4 IU and 26.4±9.8 IU at the beginning and the end. The increases were not significant (p>0.05).Side effects were not clinically seen. Trombocytopenia was on 14.3 percent of patients,it was transient and mild. Erosion on x-ray was on 71.4 percent of patients,it did not increase at the end of treatment. At the end of treatment, global effectiviness mean was 2.5±0.7 Conclusion: The present study is an open, noncontrolled and noncomparable preliminary trial. The results were positive and compatible with literature.At the end of six months, side effects were no clinically seen. The patient’s adaptation was full.Weeky usage had provided ease. The benefits of these treatments will have to be supported with longterm, randomized controlled blind study and these trials will have to be done. (Rheumatism 2007; 22: 6-10)